ANALISIS PENILAIAN PERSEDIAAN OBAT DENGAN MENGGUNAKAN METODE FIFO DAN AVERAGE DI PT TRIMITRA PHARMASI - Heliyanti (Cattleya Darmaya Fortuna, 2026)
The This study aims to analyze drug inventory valuation using FIFO and Average methods at PT Trimitra Pharmasi and identify constraints in FIFO implementation and their impact on ending inventory and cost of goods sold (COGS). This research uses a qualitative descriptive approach with data collected through observation, interviews, and documentation. Data were analyzed by calculating ending inventory and COGS using FIFO and Average methods and comparing the results. The results show that the inventory system is computerized, but FIFO implementation is not fully optimal due to inconsistent recording caused by manual input and system changes, leading to stock discrepancies and expired/damaged returns. FIFO produces a higher ending inventory value, while Average results in a lower COGS. Therefore, FIFO is more suitable for operational inventory control, while Average can be used as a comparison for inventory valuation and COGS reporting.